The Removal Of Cd, Cr, Cu, Ni, And Pb From A Synthetic Wastewater Effluent By An Environmental Bacterial Consortium - Sannasi P.; Salmijah S.; Kader J.; Othman O (Jerad Publications, Bhopal (India, 2024)
Non-Indexed Publication